Is abortion more serious than murder? - Martí Colom (Cauriensia)
Peter Singer's main interest has been practical ethics. At the level of normative ethics, Singer's moral philosophy has undergone two stages. The paper asks whether the changes at the level of normative ethics allow the Singer of the second stage to maintain the practical ethics approaches of his first stage, as he has done and as is paradigmatically shown in the successive editions of his famous book Practical Ethics. To this end, the first and second Singer's treatment of the question of the moral consideration of abortion and murder is confronted with a fairly widespread intuition, namely that murder is more serious than abortion. The conclusion is that the second Singer, unlike the first, cannot maintain his commitment to that intuition, and that Practical Ethics therefore requires an update. Finally, some possible ways in which Singer might address this situation are tentatively explored.